The influence of hyperthyroidism on implant restoration treatment outcome (Medical Journal of Indonesia, 2006)
There is limited information about bone implant restoration treatment on edentulous patient with hyperthyroidism. This clinical report is presenting the making of dental bone implant restoration on patient with hyperthyroidism history. A 60 years old male patient with hyperthyroidism came to Prosthodontic Clinic Faculty of Dentistry University of Indonesia to improve his ailing denture. After comprehensive evaluation we treated the patient with Implant-Tissue-Supported Overdenture (4 Implants) for rehabilitating upper edentulous jaw, and 2 Implant-Tooth-Supported Fixed Partial Denturesfor rehabilitating Kennedy class II lower edentulous jaw respectively. Short term clinical and radiographic evaluation based on Buserâs criteria showed positive result. (Med J Indones 2006; 15:191-5)Keywords: Hyperthyroidsm, implant restoration